Eosinophilic gastrointestinal disorders in children and adolescents: A single-center experience. Issue 2 (February 2022) - Votto, Martina; Raffaele, Alessandro; De Filippo, Maria; Caimmi, Silvia; Brunero, Marco; Riccipetitoni, Giovanna; Marseglia, Gian Luigi; Licari, Amelia
Abstract: Background: To date, few studies have been conducted in Italy on pediatric eosinophilic gastrointestinal diseases (EGIDs). Aims: To assess clinical features of pediatric patients with EGIDs who are followed in a tertiary pediatric center. Methods: From January 2015 to December 2019, we retrospectively enrolled patients with EGIDs, and collected clinical, endoscopic, and histological data. Results: We enrolled 112 patients, 75.8% were male. Mean age was 9.3 ± 4.8 years. Diagnosis of EGIDs has increased in the last two years, with non-esophageal EGIDs more prevalent than eosinophilic esophagitis (EoE) (5.1% vs. 4.4%). Approximately 30% of patients had allergic comorbidities, which prevailed in children with EoE. Autism spectrum disorders were common in patients with non-esophageal EGIDs ( p = 0.007), a statistically significant finding. In addition, esophageal atresia was associated with EoE ( p = 0.04). Most EGIDs patients had normal findings or an inflammatory endoscopic phenotype. Patients with EoE were mainly treated with proton pump inhibitors (PPIs) alone or in combination with swallowed steroids. PPIs, oral steroids, and food-elimination diets were prescribed to patients with non-esophageal EGIDs. Conclusion: This is the first Italian study revealing an increased frequency of EGIDs in a pediatric population. Further studies are needed to characterize patients with these emerging diseases.